The Christmas tree farm : a Christmas novella - Carlson, Melody (Revell, a division of Baker Publishing Group, 2024)
"In order to save the family Christmas tree farm that her sister is equally determined to sell, Madison McDowell will have to focus her efforts - and grapple with her old boyfriend who owns the neighboring farms and has plans of his own - if she's to succeed. After all, the farm deserves a second chance. And perhaps love does too"--